Burnt River

Register to add an answer

answers: 1

4 cents

Answer:

Suppose that g is the inverse of f. Let's think for a moment about what this means. In order for this to be the case, it must be true that if for all x in the domain of f, if y = f(x), then x = g(y).

From this we see that then for all x, x = f(g(x)).

Therefore, to check algerbaically, you must confirm that x = f(g(x))

Example: `f(x) = 2x + 5, g(x) = (x - 5) / 2`

`f(g(x)) = 2 ( (x-5) / 2) + 5`

`= (x - 5) + 5`

`= x = f(g(x))`

Therefore we have confirmed that g is the inverse of f. This also implies that f is the inverse of g.

307

Galli

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions